Kaupapa hauora Māori : ngā whakaaro whakahirahira o ngā kaumātua : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Māori Studies at Te Pumanawa Hauora Research Centre for Māori Health and Development, Massey University, Wellington, Aotearoa/New Zealand - Wenn, Janice (Massey University, 2006)
There is a requirement for all services within the New Zealand health system to be accredited with an established quality organisation and to demonstrate an ability to provide a measurable quality service to consumers. For Māori these requirements must make sense in Māori terms. This thesis is based on the view that, for Māori, the concept of health is more effectively expressed as hauora - optimal health and wellbeing for Māori. This thesis makes five contributions to Māori health and Māori health research. First, it identifies a responsive approach to engaging kaumātua effectively in the process of qualitative research. Second, it identifies a fundamental underlying conceptual framework – kaupapa hauora Māori as a means of understanding hauora – expressed in terms derived from kaumātua in Taranaki and Kahungunu. Third, it adapts this conceptual framework into an analytical research framework and then applies it to allow kaupapa hauora Māori (described in terms of worldview, values and ethics) to be identified from a range of data. Fourth, it critically analyses popular models of Māori health – Te Whare Tapa Whā, Te Wheke and Ngā Pou Mana. Finally, it proposes and details post-doctoral research that will translate kaupapa hauora Māori into a quality services framework/tool. “Kaupapa Hauora Māori” is a conceptual framework articulated by kaumātua, and has its origins in te ao Māori, from which the aronga or worldview is developed. The aronga is composed of the kaupapa or values and tikanga or ethics that provide kaumātua with the values base of hauora. These components have been identified by kaumātua and not only inform the concept of KHM but also inform the analytical research framework that is applied to the data. The values have been identified as a core set of values comprising whakapapa, wairua, whenua, whānau, tikanga te reo Māori, tinana, and hinengaro, and the associated tikanga is expressed as behaviour or ethics. These, together, influence the perception and understanding individuals have of their world and of hauora.
Keywords: Maori; Health and hygiene; Medical care; Hauora; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321207 Indigenous health